2017
DOI: 10.1080/02670844.2016.1274536
|View full text |Cite
|
Sign up to set email alerts
|

New approach to estimate coverage parameter in 3D FEM shot peening simulation

Abstract: Shot peening is a surface cold working process used to enhance the fatigue life of metallic parts or members. Coverage is a major parameter of shot peening process, which is defined as the percentage of the sum of peened area over the total area on the surface of the specimen. In this paper, a new method is proposed to estimate the full coverage for simulation of the shot peening process. A dynamic plastic model of the shot peening process with the aid of Matlab TM code is also presented using the finite eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The values of these variables can be controlled to formulate different RS distributions by adjusting shot peening process parameters such as the shot velocity, shot size, coverage, etc. [ 24 ].…”
Section: Residual Stress Distributionmentioning
confidence: 99%
“…The values of these variables can be controlled to formulate different RS distributions by adjusting shot peening process parameters such as the shot velocity, shot size, coverage, etc. [ 24 ].…”
Section: Residual Stress Distributionmentioning
confidence: 99%
“…This aspect must be established through systematic experimentation and then incorporated into the calculation program. It is found that increasing the hardness, velocity and size of the shot is an effective method to obtain a higher level of residual stress and a deeper residual stress zone in the target material [30]. Therefore, the shot used is a high-strength steel wire cut shot produced according to DIN8201 standard, with a hardness of 750-850 HV, which is the hardest shot for the existing 0.2 mm diameter specifications.…”
Section: Analytical Calculation Model Of Coveragementioning
confidence: 99%
“…Lin et al [28,29] found that increasing the coverage of shot peening can improve the maximum CRS value and the size of plastic strain, but has little effect on the thickness of the CRS layer and no obvious regularity on the roughness value. Pham et al [30] used finite element methods to find that coverage has a significant effect on the distribution of CRS in the AISI 4340 steel. Increasing coverage, shot speed, and shot size are effective methods for obtaining higher and deeper levels of CRS field.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the SP process, the above parameters are usually converted into generic ones (shot intensity and coverage) with the help of Almen specimens; 17,18 different combinations of SP parameters can produce the same Almen intensity, each resulting in a different RS distribution over the entire thickness. 19 SP intensity and coverage have significant effects on SP-induced RS, 20 and the number of SP treatments is also considered; 21 two SP treatments and applied prestressing 22 can optimize the distribution of compressive RS and microstructures, 23 and multiple SP treatments contribute to the formation of an impact layer with high compressive RS under moderate work-hardening conditions. 24 Also, the effects of temperature 25 and double-sided SP 26 on RS have been considered, and multivariate regression analysis has been used to evaluate the interaction between SP parameters and RS profiles.…”
Section: Introductionmentioning
confidence: 99%